Integration of Genomic and Cytogenetic Data on Tandem DNAs for Analyzing the Genome Diversity Within the Genus Hedysarum L. (Fabaceae) - Yurkevich, Olga Yu.; Samatadze, Tatiana E.; Selyutina, Inessa Yu.; Suprun, Natalia A.; Suslina, Svetlana N.; Zoshchuk, Svyatoslav A.; Amosova, Alexandra V.; Muravenko, Olga V. (Frontiers in Plant Science, 2022)
The section Multicaulia is the largest clade in the genus Hedysarum L. (Fabaceae). Representatives of the sect. Multicaulia are valuable plants used for medicinal and fodder purposes. The taxonomy and phylogeny of the sect. Multicaulia are still ambiguous. To clarify the species relationships within sect. Multicaulia, we, for the first time, explored repeatomes of H. grandiflorum Pall., H. zundukii Peschkova, and H. dahuricum Turcz. using next-generation sequencing technologies and a subsequent bioinformatic analysis by RepeatExplorer/TAREAN pipelines. The comparative repeatome analysis showed that mobile elements made up 20 - 24 % (Class I) and about 2 - 2.5 % (Class II) of their repetitive DNAs. The amount of ribosomal DNA varied from 1 to 2.6 %, the content of satellite DNA ranged from 2.7 % to 5.1 %. For each species, five high confident putative tandem DNA repeats and 5 - 10 low confident putative DNA repeats were identified. According to BLAST, these repeats demonstrated high sequence similarity within the studied species. FISH-based mapping of 35S rDNA, 5S rDNA, and satDNAs made it possible to detect new effective molecular chromosome markers for Hedysarum species and construct the species karyograms. Comparison the patterns of satDNA localization on chromosomes of the studied species allowed us to assess genome diversity within the sect. Multicaulia. In all studied species, we revealed intra- and interspecific variability in patterns of chromosomal distribution of molecular chromosome markers. In H. gmelinii Ledeb. and H. setigerum Turcz. ex Fisch. et Meyer, similar subgenomes were detected, which confirmed the polyploid status of their genomes. Our findings demonstrated a close genomic relationship among six studied species indicating their common origin, and confirmed the taxonomic status of H. setigerum as a subspecies of H. gmelinii as well as the validity of combining the sect. Multicaulia and Subacaulia into one sect. Multicaulia.